Open Source for the Enterprise - Woods, Dan; Guliani, Gautam (O'Reilly Media, Inc., 2005)
Open source software is changing the world of InformationTechnology. But making it work for your company is far morecomplicated than simply installing a copy of Linux. If you areserious about using open source to cut costs, acceleratedevelopment, and reduce vendor lock-in, you must institutionalizeskills and create new ways of working. You must understand how opensource is different from commercial software and whatresponsibilities and risks it brings. Open Source for theEnterprise is a sober guide to putting open source to work inthe modern IT department. Open source software is software whose code is freely availableto anyone who wants to change and redistribute it. New commercialsupport services, smaller licensing fees, increased collaboration, and a friendlier platform to sell products and services are just afew of the reasons open source is so attractive to IT departments. Some of the open source projects that are in current, widespreaduse in businesses large and small include Linux, FreeBSD, Apache, MySQL, PostgreSQL, JBOSS, and Perl. These have been used to suchgreat effect by Google, Amazon, Yahoo!, and major commercial andfinancial firms, that a wave of publicity has resulted in recentyears, bordering on hype. Large vendors such as IBM, Novell, andHewlett Packard have made open source a lynchpin of theirofferings. Open source has entered a new area where it is beingused as a marketing device, a collaborative software developmentmethodology, and a business model. This book provides something far more valuable than either thecheerleading or the fear-mongering one hears about open source. Theauthors are Dan Woods, former CTO of TheStreet.com and a consultantand author of several books about IT, and Gautam Guliani, Directorof Software Architecture at Kaplan Test Prep & Admissions. Eachhas used open source software for some 15 years at IT departmentslarge and small. They have collected the wisdom of a host ofexperts from IT departments, open source communities, and softwarecompanies. Open Source for the Enterprise provides a top to bottomview not only of the technology, but of the skills required tomanage it and the organizational issues that must be addressed. Here are the sorts of questions answered in the book: Why is there a "productization gap" in most open sourceprojects? How can the maturity of open source be evaluated? How can the ROI of open source be calculated? What skills are needed to use open source? What sorts of open source pro ...